RASCH ANALYSIS FOR ROSENBERG SELF ESTEEM-SCALE ADAPTATION IN ADOLESCENT SANTRI - Euis Nurjanah; Mamat Supriatna (Universitas Pendidikan Indonesia, 2022)
Self-esteem in adolescent students is one of the important aspects that must be developed to have self-confidence, respect for themselves, be motivated to study religion and general knowledge, and socialize with other students. This survey aims to examine the reliability and validity of the student self-esteem questionnaire using the Rasch model. Participants were 117 young students consisting of 41 boys and 76 girls. The quantitative approach is used as a research method and there are 40 items with a scale of 4 as the answer choices. The results of data analysis showed that the Cronbach Alpha value of 0.84 was included in the high category. The Person Reliability value of 0.78 is included in the good category. From the results of the analysis, it is known that there are 26 out of 40 valid items and the Item Reliability value is 0.97 with a special category so that to examine the self-esteem of student students, it can be measured using this instrument.